Electrocardiogram in clinical medicine - Brasy, William J; Brady, William, 1960- (United Kingdom Wiley Blackwell, 2021)
"ECG interpretation is an essential skill in the acute setting; Being able to tell the difference between a comparatively benign and/or temporary rhythmic abnormality and signs of impending cardiac arrest can literally mean the difference between life and death. It's no surprise then that Dr Brady's two books on ECGs for the Emergency Physician have been perennial best-sellers. No less important than being able to recognize clinical emergencies as evidence in ECG tracings is an understanding of the full clinical implications of the ECG reading. Such knowledge enables providers to speed treatment, order further diagnostic tests, call for specialist assistance, and in all ways enhances patient care. As Dr Brady points out, there are currently, several books that present information on ECG interpretation for acute care clinicians, but none addresses clinical medicine from the perspective of the ECG as this book will do. Dr Brady and his colleagues will address any and all interpretative issues regarding the "how do I read this ECG" consideration. BUT, they will take this important information a step further, and address what the clinician should do with this important interpretative data. Many books are rather stale missives addressing ECG interpretation in the vacuum. This book will teach and instruct ECG interpretation in the clinical realm so that readers have a complete and 3-dimensional understanding of the patient's situation, the available treatment options, what additional testing should be done, and more. In short, this book will vastly improve providers' ability to take appropriate clinical action based on ECGs seen most often in the acute setting"--
Includes bibliographical references and index.
Keywords: Electrocardiography -- methods; Heart Diseases -- diagnosis